TIBBIYOT MUASSASALARIDA ENERGIYA TEJAMKOR ARXITEKTURA: SHIFOXONA VA KLINIKALARDA ZAMONAVIY LOYIHALASH YECHIMLARI (KIUT Publication, 2025)
This article analyzes the principles of energy-efficient architecture and modern design solutions in medical institutions. The hospitals will address issues of improving energy efficiency, ensuring environmental sustainability andcreating a patient-friendly environment. It also examines how global climate change and the need to conserve resources should be taken into account when designing modern medical buildings.